A Sketch of Metals and Metalworkers in the Ancient Near East - Bjorkman, Judith Kingston
A Thesis in Oriental Studies Presented to the Faculty of the Graduate School of Arts and Sciences of the University of Pennsylvania in Partial Fulfilment of the Requirements for the Degree of Master of Arts.